E-learning del idioma inglés con plataformas online - Condori-Chura, Delia; Flores, Antonio; Cahui-Cahui, Javier; Gutiérrez, Lézany (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented to Altiplano National University that sought to determine the degree of relationship between variables: virtual platforms and the learning of the English language in university students, considering the importance of learning the English language with the use of virtual platforms in the current virtualized context due to covid-19. Methodologically, the research is of a quantitative approach, of a non-experimental type, descriptive correlational design and with transversal temporality, whose sample is not probabilistic for convenience, made up of 30 students who were given a questionnaire and an exam, the first about the use of the virtual platforms and the following exam to evaluate the four skills of the English language. The results achieved were: The use of virtual platforms has a significant weak positive connection in the development of listening comprehension in students. Likewise, a positive confirmation of significant media in the development of reading comprehension, written expression and oral expression in students. Finally, it has been determined that the use of virtual platforms has a significant average positive connection in the learning of the English language in university students of Tourism.